Hepatosplenic schistosomiasis in Zambian adults is characterized by increased liver stiffness: A nested case-control study. Issue 7 (July 2020) - Sinkala, Edford; Vinikoor, Michael; Miyanda Siyunda, Alice; Zyambo, Kanekwa; Besa, Ellen; Nsokolo, Bright; Wandeler, Gilles; Foster, Graham R.; Kelly, Paul
Abstract: Cirrhosis commonly complicates portal hypertension worldwide but in Zambia hepatosplenic schistosomiasis (HSS) dominates as the cause of portal hypertension. We need easier and non-invasive ways to assess HSS. Transient elastography (TE), a measure of liver stiffness can diagnose liver cirrhosis. TE remains unexplored in HSS patients, who generally have normal liver parenchyma. We aimed to explore liver stiffness in HSS. This nested case control study was conducted at the University Teaching Hospital, Lusaka, Zambia between January 2015 and January 2016. We enrolled 48 adults with HSS and 22 healthy controls. We assessed liver stiffness using TE while plasma hyaluronan was used to assess liver fibrosis. Plasma tumor necrosis factor receptor 1 (TNFR1) and soluble cluster of differentiation 14 (sCD14) were used to assess inflammation. The median (interquartile range) liver stiffness was higher in patients, 9.5 kPa (7.8, 12.8) than in controls, 4.7 kPa (4.0, 5.4), P < 0.0001. We noted linear correlations of hyaluronan and TNFR1 with the liver stiffness, P = 0.0307 and P = 0.0003 respectively. HSS patients seem to have higher liver stiffness than healthy controls. TE may be useful in identifying fibrosis in HSS. The positive correlations of inflammatory markers with TE suggest that HSS has both periportal and parenchymal pathophysiology. Abstract : Metabolism; Liver stiffness; Hepatosplenic schistosomiasis; Fibrosis.